Pengaruh Transformasi Digital Terhadap Kinerja Produk Aplikasi Low-Code No-Code B-Pro Bisnis Mahasiswa - Dwi Lailatun Nisa; Irsal Fauzi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Current information technology developments enable UMKM and creative endeavours to improve their business performance through the LCNC (Low-Code, No-code) Platform, as well as offer great potential for improving productivity and business development processes. The study aims to identify and analyze the impact of Privacy, Rapidity, Cost Reduction, Complexity Reduction, Easy Maintenance, Involment of Business Profile, and Minimalisation of Unstable on the performance of the Low-code No-code B-Pro Business Student application at Ngudi Waluyo University. The influence we want to know is whether it's direct or indirect. This type of research is quantitative, using 113 populations with purposive sampling techniques. The test tools used are statistical analysis methods of multivariate development of regression and path analysis. The results of this study showed that significant influence on the variables Rapidity and Involment of business profile significantly affected the performance of low-code no-code applications.